2021
DOI: 10.1017/s0022215121001821
|View full text |Cite
|
Sign up to set email alerts
|

Comparing intermediate-term hearing results of NiTiBOND and Nitinol prostheses in stapes surgery

Abstract: Objective To statistically analyse the hearing thresholds of two cohorts undergoing stapedotomy for otosclerosis with two different prostheses. Method A retrospective study was conducted comparing NiTiBOND (n = 53) and Nitinol (n = 38) prostheses. Results Average follow-up duration was 4.1 years for NiTiBOND and 4.4 years for Nitinol prostheses. The post-operative air–bone gap was 10 dB or less, indicating clinical success. The p-values for differences between (1) pre- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Today, titanium CliP® Piston or crimp prostheses are most widely used, and other materials, such as platinum wire/Teflon implants less so. In the past 20 years, studies have analysed the piston diameter [ 4 ], the method for stapedotomy [ 5 ], cement fixed crimpers [ 6 ], or the different clip types [ 7 11 ]. The few studies that have compared CliP® Piston and crimp prostheses showed no significant difference in the audiological outcome [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, titanium CliP® Piston or crimp prostheses are most widely used, and other materials, such as platinum wire/Teflon implants less so. In the past 20 years, studies have analysed the piston diameter [ 4 ], the method for stapedotomy [ 5 ], cement fixed crimpers [ 6 ], or the different clip types [ 7 11 ]. The few studies that have compared CliP® Piston and crimp prostheses showed no significant difference in the audiological outcome [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%